A Meta-Analysis of the Effects of Digital Surveillance of Workers: A Psychology Focused Approach - Ravid, Daniel M.; White, Jerod C.; Tomczak, Dave L.; Miles, Ahleah F.; Behrend, Tara S. (2020)
ABSTRACT Digital surveillance of workers, also known as electronic performance monitoring (EPM), is increasing as individuals shift to remote work. We conducted a meta-analysis of the effects of EPM on workers, while taking into account the psychological characteristics of the monitoring. We found that organizations that monitor more transparently and less invasively can expect more positive attitudes from workers. We also found that monitoring without an explicit purpose was not associated with any increases in performance. Finally, we found that regardless of monitoring characteristics, individuals tend to find EPM as stressful. Results highlight that even as advances in technology make possible a variety of ways to monitor workers, organizations must continue to consider the psychological component of work. While it is tempting to monitor based on new technological capabilities, organizations should instead rely on the principles of human resource management to guide monitoring practices. Keywords electronic performance monitoring, meta-analysis, performance management ABOUT THE AUTHOR/S Daniel M. Ravid George Washington University Dravid@gwu.edu Jerod C. White Purdue University jerodcw@gmail.com David L. Tomczak George Washington University davetomczak@gwu.edu Ahleah F. Miles George Wasingtion University afmiles@gwu.edu Tara S. Behrend Purdue University tara.behrend@gmail.com New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s)